Winter occurrence and spawning characteristics of Pacific herring (Clupea pallasii) in Jinhae Bay: An integrated survey using acoustic monitoring, gillnet sampling, and environmental DNA - Euna Yoon; Yong-Deuk Lee; Jeong-Hoon Lee; Inyeong Kwon; Hyungbeen Lee (PLoS ONE, 2026)
This study investigated the adult density, timing of migration, and biological characteristics of Pacific herring ( Clupea pallasii ) entering Jinhae Bay, South Korea, in winter, a major spawning ground for the species. A wideband autonomous transceiver (WBAT) was deployed from November 2022 to March 2023, and standardized gillnet surveys and environmental DNA (eDNA) were conducted concurrently. WBAT monitoring showed that C. pallasii school signals appeared predominantly from mid-January to mid-February, coinciding with the period during which herring were highly dominant in gillnet catches. Assessment of female reproductive maturity indicated that most individuals were ripe or spent, confirming that this period represented the peak spawning season. eDNA concentrations exhibited a sharp peak in mid-January in both surface and bottom waters and then declined steadily thereafter. Taken together, these results indicate that entry into the spawning ground begins in late-December, peaks in mid-to-late January, and declines toward late-February. By integrating acoustic, catch, and eDNA datasets, this study provides a comprehensive assessment of the timing, density, and spawning ecology of C . pallasii , offering evidence-based guidance for future resource management and spawning-ground protection in Jinhae Bay.